2018
DOI: 10.1638/2017-0172.1
|View full text |Cite
|
Sign up to set email alerts
|

APPLICATION OF 3-HYDROXYBUTYRATE MEASUREMENT AND PLASMA PROTEIN ELECTROPHORESIS IN THE DIAGNOSIS OF ASPERGILLOSIS IN AFRICAN PENGUINS (SPHENISCUS DEMERSUS)

Abstract: New alternative laboratory means are needed to improve the options for antemortem diagnosis of avian aspergillosis. In this study, 3-hydroxybutyrate was measured in plasma samples collected from a cohort of African penguins ( Spheniscus demersus) maintained under human care. Results were interpreted in combination with those of protein electrophoresis and compared with anti- Aspergillus antibody and galactomannan antigen detection. Overall, 3-hydroxybutyrate levels were found significantly increased in Aspergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 26 publications
0
29
1
Order By: Relevance
“…24 In birds with aspergillosis, marked changes in albumin and globulins have been commonly observed with striking decreases in the A/G ratio. [57][58][59]65,66 Cutoff values for albumin and A/G ratios, as determined by EPH, demonstrated a 90% negative predictive value for assessing the survival of Gentoo penguins with aspergillosis. 66…”
Section: Prognostic Valuementioning
confidence: 96%
See 3 more Smart Citations
“…24 In birds with aspergillosis, marked changes in albumin and globulins have been commonly observed with striking decreases in the A/G ratio. [57][58][59]65,66 Cutoff values for albumin and A/G ratios, as determined by EPH, demonstrated a 90% negative predictive value for assessing the survival of Gentoo penguins with aspergillosis. 66…”
Section: Prognostic Valuementioning
confidence: 96%
“…In conjunction with increases in beta globulins and 3-hydroxybutyrate, the specificity was 98%. 57 In a large study inclusive of various avian species but predominating in psittacines with confirmed or probable aspergillosis, the presence of increased beta and/or gamma globulin concentrations was associated with a 73% sensitivity and 70% specificity. 53 The diverse and dramatic electrophoretic changes with aspergillosis in the African penguin can be observed in Figure 4.…”
Section: Avian S Pecie Smentioning
confidence: 98%
See 2 more Smart Citations
“…Despite these limitations, our group has documented an electrophoretogram skewed shift observed in the plasma of an African penguin with aspergillosis . However, the composition of this shift remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%